P60 Daily fluctuations in fatigue severity and C-reactive protein in people with rheumatic diseases. (20th April 2020) - Druce, Katie L; Gibson, David S; McEleney, Keven; Meleck, Stephanie; James, Ben; Hellman, Bruce; Dixon, William G; Mcbeth, John
Abstract: Background: Fluctuations in fatigue severity are common in people with inflammatory (e.g. rheumatoid arthritis (RA)) and non-inflammatory (e.g. fibromyalgia (FM) and osteoarthritis (OA)) rheumatic diseases. We tested whether fluctuations in fatigue in RA, OA and FM were explained by fluctuations in inflammation (C-reactive protein (CRP)), pain and mood. Methods: Participants in the GIRAF (Gaining Insight into RheumAtic Fatigue) study used a patient co-configured app to report fatigue severity, pain severity and mood on a 5-point ordinal scale (increasing scores = worse state) twice daily for 7 days. Daily CRP (mg/L) was measured via dried blood spot sampling. Fluctuations in fatigue were calculated as within-day (morning to evening variability) and between-days (morning to morning; evening to evening variability). Multi-level mixed effects ordered logistic regression models tested the relationship between fluctuations in CRP and fatigue over 7 days. The relationships between fluctuations in fatigue, pain and mood were also examined. Models were adjusted for age, sex and disease diagnosis. Results: Thirty-eight people (RA:12, OA:13, FM:13) participated and contributed data on 190 (71% of eligible) days. Participants were mostly female (81.6%), with a median age of 56 years. There were no demographic differences between disease groups. Within-day changes in fatigue severity of ≥one point were observed on 97 (51.1%) days and between-days changes were observed on 52% of mornings (92/177 eligible periods) and 49.4% of evenings (85/172 eligible). Fluctuations in pain severity and mood of ≥one point were similarly common (data not shown). Median CRP levels were low (<5mg/L) across all diseases and did not fluctuate substantially between days (change ≥1mg/L:17.5% (33/189) of days). 8 participants (21.1%: RA:4, OA:2, FM:2) had "active inflammation" (CRP>5mg/L) on a total 22 (8.3%) days in the study (range:1-8 days). Fluctuations in CRP were not associated with fluctuations in fatigue (odds-ratio:1.01, 95%CI:0.83-1.22). Fluctuations in pain severity (6.93, 4.68-10.28) and mood (4.58, 3.26-6.45) were associated with fluctuations in fatigue (Table 1). Conclusion: Fluctuations in fatigue severity were common in people with rheumatic diseases. Inflammation was low and did not predict fatigue variability. Optimal management should target fatigue independently of inflammatory disease management and may benefit from modification of pain and mood. Disclosures: K.L. Druce None. D.S. Gibson None. K. McEleney None. S. Meleck None. B. James None. B. Hellman None. W.G. Dixon None. J. Mcbeth None.